Reduction of assaultive behavior following anger treatment of forensic hospital patients with intellectual disabilities. (February 2015) - Novaco, Raymond W.; Taylor, John L.
Abstract: Anger is related to violence prior to hospitalization, during hospitalization, and after discharge. Meta-analyses have established treatment efficacy in reducing anger, but few studies have addressed whether reduced anger leads to lowered aggressive behavior. This study concerns individually-delivered anger treatment, specialized for offenders with intellectual disabilities, delivered twice weekly for 18 sessions to 50 forensic hospital patients. Assessments involved patient self-report of anger, staff ratings of anger and aggression, and case records of assaultive incidents. Physical assault data were obtained from records 12 months pre-treatment and 12 months post-treatment. Significant reductions in assaults following treatment were found by GEE analyses, controlling for age, gender, length of stay, IQ, and pre-hospital violence. Following treatment, physical attacks reduced by more than half, dropping from approximately 3.5 attacks per patient 6 months prior to treatment, versus approximately 1 attack per patient in the 6–12 month interval post-treatment. In hierarchical regressions, controlling for IQ, reduction in physical assaults was associated with pre-to post-treatment change in anger level. These findings buttress the efficacy of anger treatment for patients having histories of violence and have significance for patient mental health, hospital staff well-being, therapeutic milieu, hospital management, and service delivery costs. Highlights: There are no previous studies on whether anger treatment reduces violent behavior in hospital. CBT anger treatment was delivered to forensic patients with intellectual disabilities. Physically assaultive behavior significantly reduced following anger treatment, controlling for covariates. Reduction in assaults was significantly associated with declines in anger over the course of treatment. Results have importance for patient mental health, hospital staff well-being, and hospital management and service delivery.